Enhancing Language Skills in Nigeria Adult Education: Opportunities and Challenges - Ononeze, O. F.; Okoroafor, P. E. N.; Onyenze, F. U. (Journal of Research in Adult and Continuing Education, 2025)
This study explores the opportunities and challenges of enhancing language skills in adult education programs in Nigeria, highlighting both the opportunities and challenges in promoting effective language learning among adult learners. As language proficiency is essential for personal development, civic engagement, and economic empowerment, the study examines current practices in adult literacy initiatives, the linguistic diversity of Nigeria, and the socio-economic factors influencing adult education. Opportunities such as the integration of technology, community-based learning, and bilingual education models are discussed as potential avenues for improvement. Conversely, the paper also addresses persistent challenges, including inadequate funding, limited access to qualified instructors, and the marginalization of indigenous languages. The article concludes by recommending policy reforms, stakeholder collaboration, and innovative facilitator training approaches to strengthen language acquisition in adult education, ultimately contributing to national development and lifelong learning.